2022
DOI: 10.1093/bjc/azac069
|View full text |Cite
|
Sign up to set email alerts
|

Economic Inequality and the Spatial Distribution of Stop and Search: Evidence from London

Abstract: We analyse the spatial concentration of stop and search (S&S) practices. Previous work argues that the persistent reliance on S&S, despite weak to null deterrent effects on crime, results from a social order maintenance motivation on the part of the police. Expanding previous studies that focused on who tends to be stopped and searched by police officers, we focus on where S&S concentrates and investigate the role of economic inequality. We use data from London in 2019 and demonstrate that a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Miller et al [48] found that officers with deeper implicit biases were more inclined to participate in discriminatory activities such as unfair stop-and-search strategies. They emphasised the possible effect of subconscious preconceptions on dealing with people of different races or ethnicities, as well as the impact of officer qualities and experiences on subconscious prejudices [62]. These prejudices were exemplified by officers with less experience being more likely to have larger implicit biases, highlighting the relevance of training and exposure to other communities in eliminating bias in law enforcement employees [21].…”
Section: Subconscious Bias Of Police Officersmentioning
confidence: 99%
“…Miller et al [48] found that officers with deeper implicit biases were more inclined to participate in discriminatory activities such as unfair stop-and-search strategies. They emphasised the possible effect of subconscious preconceptions on dealing with people of different races or ethnicities, as well as the impact of officer qualities and experiences on subconscious prejudices [62]. These prejudices were exemplified by officers with less experience being more likely to have larger implicit biases, highlighting the relevance of training and exposure to other communities in eliminating bias in law enforcement employees [21].…”
Section: Subconscious Bias Of Police Officersmentioning
confidence: 99%
“…There are multiple reasons that make the study of the intersectionality between ethnicity and deprivation particularly informative. For example, we can think of different mechanisms through which deprivation could be mediating the effect of race on sentencing; such as: i) considerations of rehabilitative potential affected by prospects of employment, family structure, or access to rehabilitation programs (Chen et al, 2022); ii) judicial perceptions of offenders' culpability and dangerousness affected by general perceptions of coldness, incompetence and 'otherness' commonly attributed to the poor (Kiebler and Stewart, 2022;Lindqvist et al, 2017); iii) the type of legal defence afforded (Anderson and Heaton, 2012), an inequality exacerbated in England and Wales in the last decade as a result of cuts to legal aid; v) overpolicing of more deprived areas, which are also the more highly populated by ethnic minorities (Suss and Oliveira, 2022); or vi) even more plainly, exempting the impact of prison to those perceived as more valuable members of society, which was perfectly exemplified -if anecdotally -in the case of the Oxford student Lavinia Woodward, who was exempted from a custodial sentence following the stabbing of her boyfriend to avoid damaging her promising future career as a surgeon (BBC News, 2017).…”
Section: Introductionmentioning
confidence: 99%